2014
DOI: 10.1002/elps.201300570
|View full text |Cite
|
Sign up to set email alerts
|

Biotoxin sensing in food and environment via microchip

Abstract: Biotoxin contamination in food and environmental samples has threatened health or life of human and animals. Thus, a rapid lab-independent sensing method for biotoxin determination is urgently required. Microchip sensing system allows a promising rapid and low-cost detection strategy. Herein, the recent development of various microchips, including microfluidic chip and microarray, has been discussed to sense various biotoxins in food and environmental samples (i.e. phytotoxin, animal toxin, marine toxin, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…It can readily contaminate both food and feed during almost all stages, e.g., before and after harvest and during storage, transportation, and consumption. It has been recognized that the fungal- or mycotoxin-induced diseases increasingly threaten both biodiversity and food security [ 1 ]. Recently, it is indicated that a fungal threat from AFB 1 and other mycotoxins (or fungus) could cause a 39% loss in the world's food supply if severe epidemics were to occur simultaneously on all five crops [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can readily contaminate both food and feed during almost all stages, e.g., before and after harvest and during storage, transportation, and consumption. It has been recognized that the fungal- or mycotoxin-induced diseases increasingly threaten both biodiversity and food security [ 1 ]. Recently, it is indicated that a fungal threat from AFB 1 and other mycotoxins (or fungus) could cause a 39% loss in the world's food supply if severe epidemics were to occur simultaneously on all five crops [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ relevance in remote areas, and resource limited developing countries like India due to its stability, ease of production, and use 20 . To meet this requirement, aptamer (as a biorecognition element) based detection has recently increased in demand, due to its higher specificity and lesser cross reactivity as compared to antibodies, as well as ease of production 12,21 .…”
mentioning
confidence: 99%
“…Microfluidics is an emerging technology designed for the controlled movement of small fluid volumes through a microchannel network [ 18 , 19 ]. In principle, microfluidic platforms offer the potential for a portable, simple-to-use, and inexpensive lab-on-chip device for rapid multi-analyte detection of small volume samples [ 20 , 21 , 22 ]. Indeed, a multitude of customized microfluidic solutions have been shown effective for analyte detection as R&D tools, but few have translated into successful commercial products adopted by end-users [ 18 ].…”
Section: Discussionmentioning
confidence: 99%